CINTA DALAM PERSPEKTIF AL-QUR'AN: Analisis Surah Al-Baqarah Ayat 165 - Budi Suhartawan; Muizzatul Hasanah (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
Research on love is the answer key for those who want to feel the power of the wave of love. Love is a feeling that causes pleasure to or is attached to an object, love will be emotional when it appears in the mind and can evoke all primary emotions, according to the emotions on which the object stands. However, in daily practice, many people misinterpret love and misrepresent it. This paper aims to straighten out how we should love something. The data of this research is sourced from the analysis of Surah Al-Baqarah/2:165. Based on the research results of the letter Al-Baqarah/2:165. The method used is a qualitative research method, namely analyzing the meaning and concept of love (mahabbah) from the perspective of the Qur'an. The approach used is the thematic interpretation approach (tafsir maudhu'i). Researchers found two ways to love. First, don't love something excessively and second, love it in a good way. In line with that, this paper suggests the need for the role of all elements of society, parents, teachers, lecturers, and practitioners in directing and solving love problems.